2019
DOI: 10.3389/fpls.2019.01625
|View full text |Cite
|
Sign up to set email alerts
|

RNA Splicing of FLC Modulates the Transition to Flowering

Abstract: Flowering is a critical stage of plant development and is closely correlated with seed production and crop yield. Flowering transition is regulated by complex genetic networks in response to endogenous and environmental signals. FLOWERING LOCUS C (FLC) is a central repressor in the flowering transition of Arabidopsis thaliana. The regulation of FLC expression is well studied at transcriptional and post-transcriptional levels. A subset of antisense transcripts from FLC locus, collectively termed cold-induced lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 95 publications
0
22
0
1
Order By: Relevance
“…1 Spliceosome components were demonstrated to play important roles in development via pre-mRNA splicing in Arabidopsis. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In addition to pre-mRNA splicing, subunits of the spliceosome can also mediate transcription, translation, or cell signaling. 20 Arabidopsis JANUS is a putative subunit of the spliceosome and homologous to the human spliceosome subunit SF3b4.…”
Section: Background and Discussionmentioning
confidence: 99%
“…1 Spliceosome components were demonstrated to play important roles in development via pre-mRNA splicing in Arabidopsis. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In addition to pre-mRNA splicing, subunits of the spliceosome can also mediate transcription, translation, or cell signaling. 20 Arabidopsis JANUS is a putative subunit of the spliceosome and homologous to the human spliceosome subunit SF3b4.…”
Section: Background and Discussionmentioning
confidence: 99%
“…As an important factor in post-transcriptional gene regulation, AS is intimately involved in the regulation of developmental processes such as seedling development, juvenile vegetative phase, adult vegetative phase, senescence, flowering, and circadian timekeeping (Cui et al, 2017 ; Gil et al, 2017 ; Szakonyi and Duque, 2018 ; Bai et al, 2019 ; Park et al, 2019 ; Qi et al, 2019 ). For example, the floral activator CONSTANS (CO), which plays a crucial role in photoperiodic flowering (Gil et al, 2017 ), undergoes AS producing two isoforms—the full-size physiologically functional COα and the C-terminally truncated COβ (Qi et al, 2019 ). COβ acts as a competitive inhibitor of COα by forming non-functional heterodimers which have a significantly reduced DNA binding capability compared to the COα-COα homodimers (Qi et al, 2019 ).…”
Section: The Important Roles Of As For Plant Development and Stress R...mentioning
confidence: 99%
“…For example, the floral activator CONSTANS (CO), which plays a crucial role in photoperiodic flowering (Gil et al, 2017 ), undergoes AS producing two isoforms—the full-size physiologically functional COα and the C-terminally truncated COβ (Qi et al, 2019 ). COβ acts as a competitive inhibitor of COα by forming non-functional heterodimers which have a significantly reduced DNA binding capability compared to the COα-COα homodimers (Qi et al, 2019 ). AS of polyadenylated ETHYLENE RESPONSE FACTOR4 (ERF4), a positive regulator of leaf senescence, results in two ERF4 isoforms: ERF4-R which contains the EAR-motif, and ERF4-A which lacks it (Lyons et al, 2013 ).…”
Section: The Important Roles Of As For Plant Development and Stress R...mentioning
confidence: 99%
“…In a subsequent study, overexpression of AtGRP7 was found to result significant changes in the ratios of AS isoforms in 59 out of 288 analyzed AS events [67 Cold-induced long antisense intragenic RNAs (COOLAIR) originate from the pr moter adjacent to the FLOWERING LOCUS C (FLC) 3′UTR. Two structural variants COOLAIR have been identified, terminating at proximal (sense intron 6) or distal (sen promoter) sites to repress FLC expression following cold exposure [68]. AtGRP7 has be shown to bind to FLC antisense pre-mRNA and the binding site is close to the polyaden ation site of the proximal COOLAIR structural type.…”
Section: Gr-rbp Function In As and Polyadenylationmentioning
confidence: 99%